Efficacy and safety of tildrakizumab in patients with active psoriatic arthritis: results of a randomised, double-blind, placebo-controlled, multiple-dose, 52-week phase IIb study. Issue 9 (13th May 2021) - Mease, Philip J; Chohan, Saima; Fructuoso, Ferran J Garcia; Luggen, Michael E; Rahman, Proton; Raychaudhuri, Siba P; Chou, Richard C; Mendelsohn, Alan M; Rozzo, Stephen J; Gottlieb, Alice
Abstract : Objectives: To evaluate efficacy and safety of the anti-interleukin-23p19 monoclonal antibody tildrakizumab in patients with psoriatic arthritis (PsA). Methods: In this randomised, double-blind, placebo-controlled, phase IIb study, patients with active PsA were randomised 1:1:1:1:1 to tildrakizumab 200 mg every 4 weeks (Q4W); tildrakizumab 200, 100 or 20 mg Q12W; or placebo Q4W. Patients receiving tildrakizumab 20 mg or placebo switched to tildrakizumab 200 mg Q12W at W24; treatment continued to W52. The primary efficacy endpoint was proportion of patients with ACR20 response (≥20% improvement by American College of Rheumatology criteria) at W24. Secondary efficacy endpoints were assessed without adjustment for multiplicity. Safety was evaluated from treatment-emergent adverse events (TEAEs). Results: 391/500 patients screened were randomised and treated. At W24, 71.4%–79.5% of tildrakizumab-treated versus 50.6% of placebo-treated patients achieved ACR20 (all p<0.01). Patients receiving tildrakizumab versus placebo generally achieved higher rates of ACR50, Disease Activity Score in 28 joints with C reactive protein <3.2, minimal disease activity and 75%/90%/100% improvement from baseline Psoriasis Area and Severity Index responses at W24 and through W52. Improvement in dactylitis and enthesitis was not observed; results were mixed for other outcomes. Responses in patients switched to tildrakizumab 200 mg at W24 were consistent with treatment from baseline. TEAEs and serious TEAEs occurred in 64.5% and 3.3%, respectively, of all patients through W52 and were comparable among treatment arms. Conclusions: Tildrakizumab treatment significantly improved joint and skin manifestations of PsA other than dactylitis and enthesitis. Treatment was generally well tolerated through W52. Clinicaltrials.gov NCT02980692 .